To end in fire - Weber, David, 1952-; Flint, Eric (Baen, 2021)
"The Solarian League lies in defeat, crushed by the Grand Alliance of Manticore, Haven, and Grayson. Obedient to the Alliance's surrender demands, the League is writing a new Constitution, to prevent the reemergence of out-of-control bureaucrats, like the "Mandarins" who led it to disaster. Frontier Security has been disbanded, the Outworlds' have regained control of their own economic destinies, and multiple star systems will soon secede from the League entirely"--